Model training tasks as a tool for the construction of training process for athletes in team sports - Viktor Kostyukevich; Natalia Shchepotina (National University of Physical Education and Sport of Ukraine, 2016)
The paper substantiates the design of the training process of athletes in team sports during an annual training cycle on the basis of model training tasks. The model training tasks are developed along with micro-and mesocycles, periods, and annual cycle for preparation of elite female volleyball players. The ratio of the training means and various types of training loads in the periods of macrocycle were determined. Introduction of model training tasks into the training process in team sports allows to efficiently plan and optimize the preparation of athletes, as well as to implement the principle of individualization in the development of a coherent team.